2018
DOI: 10.1038/s41467-018-06584-5
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of autism spectrum disorder candidate gene NUAK1 impairs cortical development and behavior in mice

Abstract: Recently, numerous rare de novo mutations have been identified in patients diagnosed with autism spectrum disorders (ASD). However, despite the predicted loss-of-function nature of some of these de novo mutations, the affected individuals are heterozygous carriers, which would suggest that most of these candidate genes are haploinsufficient and/or lead to expression of dominant-negative forms of the protein. Here, we tested this hypothesis with the candidate ASD gene Nuak1 that we previously identified for its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
(73 reference statements)
1
22
1
Order By: Relevance
“…Furthermore L-Carnitine and VK2 can rescue axon branching in a NUAK1 null background, without affecting significantly axon length (Fig 6). We previously reported that an autism-linked truncated NUAK1 impairs axon branching without affecting axon elongation (V. Courchet et al, 2018), although mitochondrial function has not been explored for this mutant. Taken together these observations suggest that, in cortical axons, mitochondrial function is necessary and sufficient for collateral branching.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore L-Carnitine and VK2 can rescue axon branching in a NUAK1 null background, without affecting significantly axon length (Fig 6). We previously reported that an autism-linked truncated NUAK1 impairs axon branching without affecting axon elongation (V. Courchet et al, 2018), although mitochondrial function has not been explored for this mutant. Taken together these observations suggest that, in cortical axons, mitochondrial function is necessary and sufficient for collateral branching.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we turned to microscopy-based strategies to directly investigate mitochondrial function. Cortical neuron cultures were performed from floxed NUAK1 embryos (NUAK1 F/F ; (V. Courchet et al, 2018)) in order to achieve sparse, single-cell NUAK1 inactivation. CRE recombinase encoding plasmids were electroporated together with plasmids encoding the fluorescent protein mVenus and the mitochondrial marker mito-BFP.…”
Section: Nuak1 Kinase Controls Axonal Mitochondrial Metabolismmentioning
confidence: 99%
See 3 more Smart Citations